2013
DOI: 10.1103/physrevlett.111.077201
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Magnetic Reversal in Permalloy Films Patterned into Artificial Quasicrystals

Abstract: We have patterned novel Permalloy thin films with quasicrystalline Penrose P2 tilings and measured their dc magnetization and ferromagnetic resonance absorption. Reproducible anomalies in the hysteretic, low-field data signal a series of abrupt transitions between ordered magnetization textures, culminating in a smooth evolution into a saturated state. Micromagnetic simulations compare well to experimental dc hysteresis loops and ferromagnetic resonance spectra and indicate that systematic control of magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 12 publications
2
65
0
Order By: Relevance
“…SEMPA images acquired in the field-cycled remnant state [Figs. 3(b) and 3(d)] exhibit many high-energy vertices and near-perfect mirror symmetry with respect to the magnetic field axis, which confirms the high quality of our P2T samples and verifies the existence of a “near-saturated” Ising remnant state anticipated from dc magnetization and ferromagnetic resonance studies of third generation P2T [10]. …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…SEMPA images acquired in the field-cycled remnant state [Figs. 3(b) and 3(d)] exhibit many high-energy vertices and near-perfect mirror symmetry with respect to the magnetic field axis, which confirms the high quality of our P2T samples and verifies the existence of a “near-saturated” Ising remnant state anticipated from dc magnetization and ferromagnetic resonance studies of third generation P2T [10]. …”
Section: Discussionsupporting
confidence: 77%
“…The case of P2T is much more complex, given it is an aperiodic array of Ising segments of two lengths connected at predominantly asymmetric vertices of nine types and a wide range of coordination numbers 2 ≤ N ≤ 5 [10,19,20] [see Fig. 4(a)].…”
Section: Analysis Of Sempa Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial spin ice structures have proven to be exemplary 35 systems in which to study frustration [5,6] and have been noted for their technological 36 potential as both a reconfigurable metamaterial and as a memory storage medium [7,8,37 9, 10,11,12]. Connected artificial spin ice in particular has been studied extensively in 38 the last decade [13,14,15,16,17,18,19,20,21,22,23,24,25]. Tanaka et al and 39 other workers, observed sharp features in the magnetoresistance of connected artificial 40 spin ice, and associated them with reversal events that maintain the ice rules of the 41 system [13,14,15].…”
mentioning
confidence: 99%
“…In this collection, Morrison et al [13] suggest an alternative route to achieve a highly degenerate artificial spin system that is not a result of the degeneracy of the vertex configurations, but rather a consequence of the arrangement of non-degenerate vertices. The creation of quasiperiodic structures [14], containing varying numbers of neighbouring nanomagnets at the vertices, therefore opens the way to tailor the ground state degeneracy and to discover of novel phenomena in artificial spin ice such as channels of specific vertex types [13] that may act as conduits for transport of magnetic charges [15,16]. The consequence of The magnetization direction within the arms of the array can be determined from the detailed intensity profile across the arm [8], allowing the magnetic charge at each vertex to be inferred.…”
Section: Control Of Magnetic Configurations Via Topology and Geometrymentioning
confidence: 99%